Peran Komunikasi Pemangku Adat Nagari Padang Laweh Dalam Mengatasi Sengketa Tanah Ulayat - Oktavia, Fadila; ., Defhany (CV. ITTC INDONESIA, 2024)
This research aims to examine the role of traditional leaders' communication in Nagari Padang Laweh Malalo in resolving customary land disputes in Tanah Datar Regency. Customary land disputes often lead to prolonged and complex conflicts within indigenous communities. To address this issue, the study employs a qualitative approach, gathering data through semi-structured interviews with traditional leaders and direct field observations. The findings indicate that traditional leaders play a vital role in mediating and resolving disputes, which serves as a benchmark in customary land conflict resolution. They prioritize consensus-building and active community participation in the conflict resolution process. Respect for traditional customs has proven effective in achieving fair and sustainable solutions. Additionally, collaboration among traditional leaders, government authorities, and legal institutions strengthens efforts to resolve disputes, thereby fostering harmony and stability within the community. In conclusion, this study confirms that effective communication and mediation strategies rooted in customary values are key to addressing customary land disputes in Nagari Padang Laweh Malalo. These findings provide valuable insights for managing land conflicts in other indigenous communities and reinforce the role of traditional leaders in promoting peace and justice within society